Investment Behavior by American Railroads: 1897-1914 - Neal, Larry (The Review of Economics and Statistics, 1969)
HE major contention of this paper is that T American railroad investment behavior in the period 1897-1914 is best understood by emphasizing the role of financial factors, in spite of the fact that the accelerator theory from its inception has been most successfully applied to railroad investment in precisely this period [3, 11, 12]. (This was also true in Tinbergen (17) although Tinbergen preferred a model using profits as the explanatory variable.) This argument is also in direct contradiction to the recent explanation of railroad investment behavior in this period advanced by Kmenta and Williamson [10] . The argument rests upon significant changes in railroad finance which occurred at the beginning of the period. These permitted easier access to funds from sources external to the individual companies and likewise permitted more internal funds to be used for capital formation. This encouragement of investment due to easier financing was ended, however, by the Panic of 1907. These financial changes are sufficient to vitiate any form of the accelerator explanation of investment behavior which depends upon a fixed accelerator coefficient and a fixed lag structure of investment response to changes in demand for the period 1897-1914 as a whole. The argument is tested by comparing the effectiveness of alternative regression equations in explaining the investment behavior indicated by new estimates of railroad capital formation prepared for this study. Tihe new estimates are designed to remedy the defects existing in those published by Ulmer [18] . The results of the testing may be summarized most easily by reference to the Kmenta-Williamson hypothesis that investment behavior in American railroads is best explained by models appropriate to the various phases of the industry's life cycle. The model they chose to explain investment behavior in the phase 1897-1914 is described by the equation I = a, + a2 (RX.K_.) where I = net investment in 1929 dollars (Ulmer's estimates), X = output in 1929 dollars, and K = net capital stock (first of year). One conclusion of this paper is that this particular model is inferior to a model emphasizing the costs of financing investment. Of more general significance is the fact that models of investment behavior which incorporate financial variables and which have performed satisfactorily for more recent periods in the railroad and other industries also do quite well in the period 1897-1914. This disputes the notion that it is more efficacious to take separate phases of industry life cycles in order to explain investment behavior.